Association of Out-of-Home Eating with Anthropometric Changes: A Systematic Review of Prospective Studies - NAGO, EUNICE; Lachat, Carl; DOSSA, ROMAIN A. MARC; Kolsteren, Patrick (My University, 2014)
In the present review, the association of out-of-home eating with anthropometric changes was examined. Peer-reviewed studies in eight databases were searched, and 15 prospective studies were included in the review. The quality of the data wasassessedbyconsideringrisksof biasinsample selection, datacollection methods, andthe appropriateness ofstatistical tests. From this, seven studies, which used relatively large samples or had a follow-up period longer than 10 years, were retainedforfurtheranalysis.Itwasconcludedthateatingout-of-homefrequently,inthebroadsense,ispositivelyassociated with the risk of becoming overweight or obese and weight change. With regard to speciﬁc out-of-home sources, the review shows that eating at fast-food outlets is associated with a greater increase in body weight and waist circumference over time than eating at restaurants and takeaway foods positively predict BMI change in women. More research is needed on out-of-home foods other than fast-foods and restaurant foods, such as street, canteen, and school foods.
Keywords: Overweight; obesity; lifestyle; diet